EVALUATION OF ENDOTHELIN-1 AND GLYCATED HAEMOGLOBIN IN TYPE 2 DIABETIC PATIENTS WITH AND WITHOUT RETINOPATHY - DOMNGANG, Christelle; DEFFO, Alex; EYOMBO, Stephanie; YOUTE, O’Neal; TEDONG, Leonard; KAGMENI, Giles; SOBNGWI, Eugene (International Journal of Retina, 2024)
Introduction: Diabetic retinopathy (DR) can lead to blindness and therefore requires early diagnosis and careful monitoring. Method: The present cross-sectional analytical survey assessed endothelin-1 (ET-1) and glycated haemoglobin (HbA1C) levels, two DR markers, in type 2 diabetic patients with and without DR in the National Obesity Centre of the Yaoundé Central Hospital in Cameroon, from February 1 to July 31, 2021. It was carried out on DR and non-DR patients, and non-diabetic patients. Various clinical parameters related to diabetes were collected, and a comprehensive ophthalmological examination as well as an analysis of HbA1C and ET-1 in participants’ blood samples were performed. Results: A total of 12 DR participants, 32 non-diabetic participants, and 45 diabetic participants without DR were enrolled. The majority of diabetic patients did not have a good HbA1C level, without a statistical difference (p-value = 0.702) between DR (75%) and non-DR (80%) patients. For ET-1, it was recorded high serum levels in diabetic patients (10.9 pg/mL [10.00 – 19.50]) compared (p-value = 0.04) to non-diabetic patients (10.6 pg/mL [6.3 – 13.5]). Moreover, DR patients recorded serum levels of ET-1 greater than (p=0.03) non-DR patients (13.1 pg/mL [10.89-21.42] vs 10.8 pg/mL [10.00-18.9]). Conclusion: These biomarker levels are a warning in DR evolution of diabetic patients. ET-1 could be a better control biomarker than HbA1c in the clinician management of DR according to this study. Thus, it is necessary to improve the description of these biomarkers in order to reinforce their use.